Chaetozone corona (Polychaeta, Cirratulidae) in the Bay of Biscay: a new alien species for the North-east Atlantic waters?. (21st April 2016) - Le Garrec, Vincent; Grall, Jacques; Chevalier, Claire; Guyonnet, Benjamin; Jourde, Jérôme; Lavesque, Nicolas; Bonifácio, Paulo; Blake, James A.
Abstract : The cirratulid species Chaetozone corona is reported for the first time from the North-east Atlantic waters. Several specimens were collected during oceanographic surveys between 1996 and 2015 from soft bottom habitats along the coasts of Brittany (Western France). This species, originally described from the coast of California, was recently recorded for the first time from the Mediterranean Sea. We hypothesize that this species could have been recently introduced to the Atlantic coasts of Europe and colonized the northern coast of Bay of Biscay from the Loire estuary to the Iroise Sea. We discuss the potential vectors of introduction and the main environmental factors that could explain its current distribution. An identification key to all the known North-east Atlantic species of Chaetozone is given.